Go Green: Memberdayakan Masyarakat Rawa Buntu Serpong Dengan Menanam Sayuran dan Rempah-rempah - Sudarmanto, Eko; Aulia, Triana Zuhrotun; Siregar, Indra Gunawan; Erdawati, Lena; Isrok Isrok; Saputra, M Wahid; Purnamasari, Yuana Fasya (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
The "Go Green: Empowering the Rawa Buntu Serpong Community through Planting Vegetables and Herbs" program is an initiative designed as part of the Community Service activities within the Integrated Community Service Program (KKN) of Universitas Muhammadiyah Tangerang (UMT). This program aims to address environmental issues while simultaneously strengthening food security in the Rawa Buntu area. By encouraging active community participation, the program promotes gardening activities in home yards or available vacant land, thus creating a greener and healthier environment. The "Go Green" program not only focuses on environmental aspects but also emphasizes the importance of economic empowerment and community self-reliance. Through the cultivation of vegetables and herbs, the community is expected not only to meet their own food needs but also to potentially increase their income through the sale of harvested produce. This initiative aims to raise awareness of the importance of urban agriculture and its contribution to environmental health and food security. The conclusion of this program demonstrates that community involvement in gardening activities not only positively impacts the environment but also strengthens the local economy and fosters more sustainable food security in the future.